2022
DOI: 10.1007/s42977-022-00118-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of novel plekhm1 and def8 mutant alleles in Drosophila

Abstract: Lysosomal degradation of cytoplasmic components by autophagy ensures the continuous turnover of proteins and organelles and aids cellular survival during nutrient deprivation and other stress conditions. Lysosomal targeting of cytoplasmic proteins and organelles requires the concerted action of several proteins and multisubunit complexes. The core components of this machinery are conserved from yeast to humans and many of them are well-characterized; however, novel molecular players have been recently discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Human and Drosophila proteins highlighted domain and sequence conservation, with Def8 positive immunoreactivity in flies, which allowed us to establish a structural homology in both species. Previous reports confirmed a strong link between Def8 and other autophagy components, Rab7a and Plekhm1 21 , 44 . Our network analyses also confirmed those observations in Drosophila .…”
Section: Discussionmentioning
confidence: 63%
“…Human and Drosophila proteins highlighted domain and sequence conservation, with Def8 positive immunoreactivity in flies, which allowed us to establish a structural homology in both species. Previous reports confirmed a strong link between Def8 and other autophagy components, Rab7a and Plekhm1 21 , 44 . Our network analyses also confirmed those observations in Drosophila .…”
Section: Discussionmentioning
confidence: 63%
“…Most research supports the idea that mammalian PLEKHM1 binds to Rab7, the HOPS complex, and GABARAP (gamma-aminobutyric acid receptor-associated) family proteins, which promotes the fusion of lysosomes with late endosomes and autophagosomes [ 1 ]. Surprisingly, Maruzs et al [ 82 ] reported that the novel mutant alleles of Drosophila, plekhm1 and def8 , do not have obvious influences on autophagy in Drosophila.…”
Section: Molecular Pattern Of Osteopetrosismentioning
confidence: 99%